단원자 촉매 합성에서의 탄소지지체 구조 특성변화에 따른 산소환원반응 성능 연구 - 김정운; 장혜진; Jungwoon Kim; Hyejin Jang (전기화학회지, 2024)
In this study, the influence of different structural characteristics of porous carbon supports with the same phase on the formation and performance of single-atom catalysts was investigated. To confirm the differences in the synthesis of iron single-atom catalysts according to the structural characteristics of porous carbon supports, carbon supports with varying specific surface areas, crystallinity, and pore volumes were used while applying the same synthesis method. The formation of single-atom catalysts on the surface of each carbon support was confirmed through X-ray diffraction (XRD) analysis and transmission electron microscopy (TEM). The oxygen reduction reaction (ORR), a representative catalytic reaction, was selected as the model reaction to evaluate the performance of the single-atom catalysts synthesized on each carbon support, and the performance was evaluated using the rotating disk electrode (RDE) method. As a result, the carbon support with the highest specific surface area exhibited the best performance. Specifically, the most superior carbon support showed a half-wave potential of 0.88 V in an acidic electrolyte environment. These results demonstrate that the structural characteristics of carbon supports significantly affect the performance of single-atom catalysts and are expected to provide an important research foundation for improving the performance of hydrogen fuel cells in the future. 본 연구에서는, 동일상을 갖는 다공성 탄소지지체에서 상이한 구조 특성이 단원자 촉매의 형성과 성능에 미치는 영향을 조사하였다. 다공성 탄소지지체의 구조 특성에 따른 철 단원자 촉매 합성의 차이를 확인하기 위해 동일한 합성법을 적용하면서 비표면적, 결정화도 및 기공부피가 다른 탄소지지체를 사용하였다. X-선 회절 분석 및 투과전자현미경 분석을 통해 각각의 탄소지지체 표면상 단원자 촉매 형성을 확인하였다. 각 탄소지지체에 합성된 단원자 촉매의 평가를 위해 대표적 활성 반응인 산소환원반응을 모델 반응으로 지정하였으며, 성능 평가는 회전전극시험법을 통해 이루어졌다. 결과적으로 다양한 구조 특성 중 비표면적이 높은 탄소지지체에서 뛰어난 성능을 나타냈다. 특히, 가장 우수한 성능을 보인 탄소지지체는 산 전해질 환경에서 반파전압이 0.88 V로 나타났다. 이러한 결과는 탄소지지체의 구조 특성이 단원자 촉매의 성능에 큰 영향을 미치는 것을 보여주며, 향후 수소 연료전지의 성능 향상을 위한 중요한 연구 기반을 제공할 것으로 기대한다.